Multiple-Choice Questions in Basic Biomedical Science Module - Made Bayu Permasutha; Gandes Retno Rahayu; Made Kurnia Widiastuti Giri; Dewa Agung Gde Fanji Pradiptha (Jurnal Pendidikan dan Pengajaran, 2024)
The evaluation process in medical education involves evaluating knowledge, skills, and attitudes based on the achievements and competencies to be achieved. The multiple-choice question (MCQ) instrument is an assessment instrument often used in the medical field. So far, the MCQs have been implemented in Indonesia's national medical competency examination. Furthermore, maintaining the quality of MCQs at the faculty level is very important to maintain the quality of medical graduates. In this study, an evaluation was carried out on 250 items of MCQs in three basic biomedical modules, followed by analyses of the MCQs characteristics, item difficulty index (DIF-I), and item discrimination index (DI).  The analysis found that the Kr-20 value was >0.8 in the three modules. Analysis of the item difficulty index (DIF-I) in the ideal category obtained 33 (36.7%), 29 (38.7%), and 34 (39.5%), respectively. The ideal category's item discrimination index (DI) was 63.3%, 77.3%, and 69.4%, respectively. The results of this study illustrate that there are still MCQs that are not ideal and need attention for future improvements. These results prove that more work must be done to improve the standard of MCQs used in medical examinations. Periodic evaluation and training on making standardized multiple-choice question components need to be planned within the faculty.